The screams of “The Scream” by Gabriela Mistral - Acero, Nibaldo (2026)
In this essay we will read Gabriela Mistral's poem “El Grito”, written in 1922, in order to analyze it in virtue and in the complexity of its own social, historical, and political context. This epochal critical exercise will link a situated (Haraway, 2021), psychobiological, and aesthetic reading with the aim of exploring the intentions, the turns, the expectations, and the fears that the Chilean poet possessed regarding Latin America at a key moment. In a very complex time for Latin America, Mistral's incisive poetics and hard integrity adopt strategies for the survival of the diversity of our subcontinent, but above all, the material and spiritual survival of a region in the vortex of its development. She calibrates intellectual passion and reason, tempering a word that is quite complex to interpret; therefore, we articulate from different analytical perspectives an interdisciplinary methodology that can forcefully address the desires of the poet, embedded in this emblematic poem.